If you strike a woman: an analysis of how women are represented in political cartoons of South Africa's Women's Day, 2009-2017 - Levin, Bianca (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
On 7 August 2017, two days prior to South Africa's National Women's Day, video footage of a representative of the State, Mduduzi Manana, beating up a woman went viral. This marred the Women's Day celebrations of that year, as it became clear to the public that the he was not going to be punished. As important political commentators, cartoonists used Manana's actions as an opportunity to depict the violence women face, even in a month dedicated to women. In these cartoons, Manana became the face of a patriarchal system, one which has deeply affected the quality of life for women who, to date, cannot claim their Constitutional rights. This thesis is interested in the mini-narratives of such cartoons, ones which offer a view on the status of South African women. Through this qualitative study, a textual analysis in the spirit of Critical Discourse Analysis of seven selected cartoons leads to a discussion of what their representations of women means for gender justice. What this research shows is that the representations that cartoons offer of the position of women in South Africa are complex. These cartoons articulate that South Africa has a long way to go to reach equality and gender justice. In order for gender justice to be realised, the representation of women needs to evolve into one which recognises women's plight but does not relegate them to the state of victimhood.
Keywords: Caricatures and cartoons -- South Africa; Women in mass media -- South Africa; Political cartoons -- South Africa